Optimal paths in the endogenous AK class growth models - Panek, Emil (Economics and Business Review, 2010)
The AK class models are simple visions of economic dynamics, where production level is determined by quantity of physical capital at economy's disposal and efficiency of its usage in the process of production. One assumes implicitly that technological conditions unambiguously define the level of technical endowment of labor (the ratio of capital to labor) and labor resources are so abundant that they serve any quantity of capital. In the paper we show that even in such simple aggregated models of economic dynamics, where an endogenous growth mechanism of capital efficiency works (due to investments and innovations by R&D), it is possible to achieve social welfare, measured by production and consumption p.c., which is not attainable on the grounds of the neoclassical growth model. (original abstract)